Analisis Pengaruh NPL, NIM, LDR, Dan CAR Terhadap Profitabilitas (ROA) Pada Bank Pemerintah Konvensional Yang Terdaftar Di BEI - Fanny Fanny; Winnie Wijaya; Indahwati Indahwati; Moni Silcya; Viendy Celine Wijaya; Wenny Anggeresia Ginting (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
The performance of a company can be said to be good if its financial statements show an increase in profits. Of course, many aspects that affect a company in generating profitability. This study aims to understand the effect of NPL, NIM, LDR, and CAR on Profitability (ROA) in banking companies both Government Banks and Conventional Banks. This research uses quantitative methods, where data sources use secondary data. By using classical assumption test analysis techniques, F test, and t test results obtained for this study are that NPL negatively and significantly affects ROA, NIM positively and significantly affect ROA, LDR negatively and significantly affect ROA, CAR positively and significantly affect ROA. NPL, NIM, LDR, and CAR simultaneously affect ROA on government banks and conventional banks listed on the Indonesia Stock Exchange in the 2014-2017 period.